Intra-arterial abciximab for the treatment of thrombus formation during coil embolization of intracranial aneurysms. (27th May 2010) - Linfante, Italo; Etezadi, Vahid; Andreone, Vincenzo; DeLeo, Michael; Alehashemi, Sara; Shaw, Kate; Wakhloo, Ajay
Abstract : Background and purpose: Thrombus formation during endovascular embolization of intracranial aneurysms occurs in 2.9%–6% of patients. Use of IIb/IIIA inhibitors such as abciximab or eptifibatide intravenously has been reported in management of this complication. Because the intra-arterial infusion of IIb/IIIA inhibitors may require lower doses to achieve thrombolysis, it may reduce the risk of haemorrhage. Therefore, we retrospectively analyze our database and review the literature. Methods: This is a retrospective analysis of a prospectively acquired database of patients with ruptured or unruptured aneurysm treated intra-arterially for thrombus formation during endovascular coil embolization between July 2005 and August 2008. Patient demographics, aneurysmal characteristics, procedural, clinical outcome and complications were recorded. Results: From July 2005 to August 2008, out of 184 patients who underwent coil embolization, 19 patients (15 smokers, 14 female, mean age 52) developed intraprocedural thrombus formation and received intra-arterial abciximab treatment. Mean aneurysm size was 6.6 mm±4.9 mm; neck size was 3.8 mm±2.1 mm. Eight (42.1%) aneurysms were ruptured. Most aneurysms (63.1%) were in anterior communicating and middle cerebral arteries. Thrombus was visualized in all cases by angiogram and treated intra-arterially with a mean dose of 10.5 mg±4.2. There were no periprocedural hemorrhagic complications. No deaths or other complications occurred during follow-up. Conclusion: Thrombus formation during coil embolization of intracranial aneurysms occurred more in women and smokers. Low doses of intra-arterial abciximab may be effective in the thromboembolic complications occurring during endovascular embolization of intracranial aneurysms.